Analisis Perilaku Kurs Rupiah Terhadap Dolar AS Selama Empat Periode Pemerintahan di Indonesia Metode Box-Jenkins (ARIMA) - Agus Arifin (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2009)
This research attempts to analyze the behavior of exchange rate (Rp/US) over the period 1998-2007 which passed four governments: Habibie, Gusdur, Megawati, and SBY. The method using in this research is Box-Jenkins with Autoregressive Integrated Moving Average (ARIMA). It tested various models to find the best one and then using it to forecast the behavior of exchange rate. The data needed in this research is only exchange rate (Rp/US) over the period 1998-2007. The research results show: (1) The best model is AR(1); (2) The forecasting of exchange rate behavior until the end of 2007 shows the stability with average value at Rp9417,13; (3) There is no significantly structural changes among four governments. Keywords: Box-Jenkins, ARIMA, exchange rate